Lexical competition in non-native spoken-word recognition - Weber, Andrea; Cutler, Anne (Journal of memory and language, 2004)
Four eye-tracking experiments examined lexical competition in non-native spoken-word recognition. Dutch listeners hearing English fixated longer on distractor pictures with names containing vowels that Dutch listeners are likely to confuse with vowels in a target picture name ( pencil, given target panda) than on less confusable distractors ( beetle, given target bottle). English listeners showed no such viewing time difference. The confusability was asymmetric: given pencil as target, panda did not distract more than distinct competitors. Distractors with Dutch names phonologically related to English target names ( deksel, ‘lid,’ given target desk) also received longer fixations than distractors with phonologically unrelated names. Again, English listeners showed no differential effect. With the materials translated into Dutch, Dutch listeners showed no activation of the English words ( desk, given target deksel). The results motivate two conclusions: native phonemic categories capture second-language input even when stored representations maintain a second-language distinction; and lexical competition is greater for non-native than for native listeners.